Internal solitary waves observation and feature extraction based on wavelet transform by Sentinel-1A in Lombok Strait, Indonesia - Chonnaniyah, Chonnaniyah; Osawa, Takahiro; Karang, I Wayan Gede Astawa (International Journal of Environment and Geosciences, 2024)
Lombok Strait is an essential pathway in trans-oceanic water mass transport. Due to this water mass transport flowing over Indonesian waters, the current is known as Indonesian Throughflow (ITF), which plays a role in the transfer of warm water masses from the Pacific to the Indian Ocean annually. Lombok Strait has intensive characteristics of the internal waves (IWs) generation because of the strong current that passes through the complex bathymetry along the strait area. IWs with large amplitude and nonlinear properties are known as Internal Solitary Waves (ISW) that can be detected by Synthetic Aperture Radar (SAR) images. A Wavelet Transform method for ISW feature extraction was applied to SAR images by Sentinel-1A (C-band). ISW packet characteristics can be distinguished from other phenomena based on their geometrical structure and shape. ISW packet pattern consists of light and dark lines which decrease intensity from front to rear. SAR observation detected 5 parameters (phase speed, soliton numbers, wavelength, first crest length, and propagation direction). The arc-like ISW in the Lombok Strait propagated to the North of the sill with average phase speeds of about 2.13 m/s and was frequently detected during the northwest monsoon (NWM). The detected soliton number is less than 6 solitons per packet with a wavelength of about 1 – 4 km, and the first crest length varies from about 12.16 km to more than 100 km. ISW detected in Sentinel-1A images were located at the bathymetry about 800 meters around the Lombok Strait area.